Usage of vaccines and therapeutics in public health emergencies 2 - Kobinger, Gary (Henry Stewart Talks, 2020)
Specific tools including vaccine and therapeutics to control outbreaks, Improved non-viral DNA-based and viral VSV-based vaccines, Recent outbreaks in Likati and North Kivu, New strategies to rapidly develop novel immune therapies and vaccines, Applications against Ebola virus and others high consequence pathogens, Recent findings on rapid vaccination regimens and their promising potential